The GLR failure detection algorithm for a class of nonlinear dynamic models with application to radar tracking problems - Janczak, D.; Grishin, Y.P. (2008 International Radar Symposium, 2008)
The paper describes a failure detection algorithm adapted to the target maneuver detection. It is supposed that the target dynamics is non-linear and the maneuver is described by the Gaussian-Markov additive models.